Interpretation of 1D-Resistivity Data to Describe the Aquifer Model in the Serayu Watershed Area of Somagede Village, Somagede District, Banyumas Regency - Sehah Sehah; Hartono Hartono; Zaroh Irayani; Urip Nurwijayanto Prabowo; Fajar Apriyanto; Desty Maharani Sagita; Dwi Purnamasari (Jurnal Geologi dan Sumberdaya Mineral, 2021)
Acquisition of resistivity data using the Schlumberger configuration has been carried out in the Serayu watershed area of Somagede Village, Somagede District, Banyumas Regency. The purpose of this research was to describe a groundwater aquifer model based on the interpretation of 1D-resistivity data. The research results are resistivity logs of subsurface rock distributed over seven sounding points with resistivity values ranging from 2.24-192.78 m. The sounding points are located at positions of 7°31′28.55″ and 109°19′8.65″ (Sch-1) to 7°31′18.79″ and 109°19′21.45″ (Sch-7). The interpretation of the resistivity logs has resulted in a lithology log at each sounding point. Based on the interpretation, the lithology of the research area is composed of topsoil (42.85-85.13 m), sandy clay which partly slightly wet (7.08-17.18m), sandy clay inserted with gravel (22.44-31.70 m), sand, gravel, and pebble, with various consolidated (22.16-192.78m), sand inserted by gravel (6.77m), alternating sandstone and claystone, some of which are alternated with marl and tuff (8.71-21.99m), and sandstones with various porosity (3.25-8.76m). Shallow aquifers are interpreted to exist in sand inserted by gravel layer (13.23-27.67 m) at the sounding point of Sch-2 where the potential is quite good. While deep aquifers are estimated to be present in the sandstone layer with various porosity (> 46.67 m) at all sounding points with very good potential.Keywords: 1D-resistivity, Serayu watershed, resistivity log, aquifer, Somagede Village.